Engaging youth in research planning, design and execution: Practical recommendations for researchers. (1st June 2018) - Hawke, Lisa D.; Relihan, Jacqueline; Miller, Joshua; McCann, Emma; Rong, Jessica; Darnay, Karleigh; Docherty, Samantha; Chaim, Gloria; Henderson, Joanna L.
Abstract: Context: Engaging youth as partners in academic research projects offers many benefits for the youth and the research team. However, it is not always clear to researchers how to engage youth effectively to optimize the experience and maximize the impact. Objective: This article provides practical recommendations to help researchers engage youth in meaningful ways in academic research, from initial planning to project completion. These general recommendations can be applied to all types of research methodologies, from community action‐based research to highly technical designs. Results: Youth can and do provide valuable input into academic research projects when their contributions are authentically valued, their roles are clearly defined, communication is clear, and their needs are taken into account. Researchers should be aware of the risk of tokenizing the youth they engage and work proactively to take their feedback into account in a genuine way. Some adaptations to regular research procedures are recommended to improve the success of the youth engagement initiative. Conclusions: By following these guidelines, academic researchers can make youth engagement a key tenet of their youth‐oriented research initiatives, increasing the feasibility, youth‐friendliness and ecological validity of their work and ultimately improve the value and impact of the results their research produces.